2018
DOI: 10.1111/jpm.12506
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotion regulation, coping, self‐reflection and insight in staff interaction with patients with a diagnosis of personality disorder in forensic settings

Abstract: Accessible summary What is known on the subject? Interaction between staff and patients with a diagnosis of personality disorder in forensic settings is important for quality of care, but research is lacking on what determines this interaction. What the paper adds to existing knowledge? Insight, emotion‐focused coping and emotion regulation of staff influence the interaction between staff and these patients. Staff who understand their own thoughts, feelings and behaviour better (more insight) needed less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…CMT is an emotion‐regulation intervention and for this reason hypothesized to be particularly useful within high‐stress work environments such as mental healthcare settings. Indicatively, a recent study (Oostvogels, Bongers, & Willems, 2018) showed that emotion‐focused coping and emotion‐regulation influenced the interaction between staff and patients with a personality disorder diagnosis, helping them to offer compassionate care and to avoid burnout. In a discussion of the design of compassionate care, Crawford et al (2014) suggest that providing a welcoming environment, promoting bidirectional compassion, providing training in compassion to healthcare professionals and involving service users, practitioners and leaders in creating supportive organizational structures might engender more compassionate and ethical working environments.…”
Section: Introductionmentioning
confidence: 99%
“…CMT is an emotion‐regulation intervention and for this reason hypothesized to be particularly useful within high‐stress work environments such as mental healthcare settings. Indicatively, a recent study (Oostvogels, Bongers, & Willems, 2018) showed that emotion‐focused coping and emotion‐regulation influenced the interaction between staff and patients with a personality disorder diagnosis, helping them to offer compassionate care and to avoid burnout. In a discussion of the design of compassionate care, Crawford et al (2014) suggest that providing a welcoming environment, promoting bidirectional compassion, providing training in compassion to healthcare professionals and involving service users, practitioners and leaders in creating supportive organizational structures might engender more compassionate and ethical working environments.…”
Section: Introductionmentioning
confidence: 99%
“…This includes good multidisciplinary working and group supervision utilising a reflective approach. Reflective discussion was recommended in Oostvogels, Bongers, and Willems (2018) study to enhance compassionate behaviour of practitioners working with service users with a personality disorder diagnosis. Yildiz (2019) highlight students' need for supervision due to their encounter of communication barriers when caring for service users and experiencing the effects of countertransference.…”
Section: Discussionmentioning
confidence: 99%
“…Gross ( 1998 ) argued an early strategy in this process, which is referred to as emotional regulation, implies suppressing or reappraising one’s emotions. This is strongly correlated with carers’ behaviour towards forensic patients, as they become less antagonistic by reducing self-criticism and increasing self-compassion (Oostvogels et al, 2018 ). Carers who avoid dealing with and managing their emotions risk becoming distanced, detached or disengaged (Oates et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%